Malaysian Preventive Detention Laws: Old Preventive Detention Provisions Wrapped in New Packages - Naz, Safia; Shamsuddin, Johan (Journal of Malaysian and Comparative Law, 2018)
Preventive detention has become a common feature of the modern democracies, including Malaysia. The Malaysian Federal Constitution in Article 149 allows the enactment of preventive detention laws without the precondition of an emergency. The Internal Security Act (ISA), 1960 was the first preventive detention law which was passed under this constitutional provision. It was enacted to deal with the armed insurgencies of the Communist Party of Malaya (CPM) and permitted the Executive to keep individuals in preventive custody for indefinite periods of time. However, a series of amendments were introduced into the ISA, which drastically broadened the scope of the exercise of the power of preventive detention by inserting new grounds of preventive detention. Additionally, an amendment introduced in 1989 took away the authority of the courts to review the lawfulness of the detention orders. The life of the ISA ultimately came to an end in 2012 when the government repealed it in the face of constant criticism from opposition political parties and human rights organisations. However, the government subsequently brought back the old draconian provisions of the ISA through the enactment of three new security laws, namely, the Security Offences (Special Measures) Act, 2012 and the Prevention of Crime (Amendment and Extension) Act, 2014 and the Prevention of Terrorism Act, 2015. Since there is a dearth of literature concerning the extent and implications of the exercise of the power of preventive detention under the new security Acts, a comparative analysis of these laws has been carried out in this Article to demonstrate how the new laws are reincarnations of the old ISA.